Acknowledging the innate impact of an information technology for engaging people in knowledge work: the case of weblog technology. (13th January 2009) - Kaiser, Stephan; Muller-Seitz, Gordon
Today, globally operating enterprises increasingly rely upon Information Technology (IT) for knowledge exchange, even though this does not inevitably result in the assumed enhancements. The impact of IT itself remains rather ambiguous. Guided by Actor-Network Theory (ANT), this paper draws on a 28-month qualitative case study and elucidates the inherent impact of a novel IT phenomenon, corporate blogospheres. A blogosphere consists of weblogs, websites where individuals publicly display their ideas in the form of a diary. Our results indicate that a blogosphere constitutes a powerful actor on its own that is capable of structuring knowledge work. Further, we illustrate how the blogosphere is efficiently organised and maintained by means of the complex interplay between various human as well as nonhuman actors. We conclude with critical reflections and an outlook for future research.